Factors influencing implementation of Malaysia Sustainable Palm Oil (MSPO) among smallholder at Tangkak, Johor, Malaysia / Hafiz Md Ali - Md Ali, Hafiz (Faculty of Plantation and Agrotechnology, 2018)
The Climate change that occurs in recent years caused certain country starting to worry about the future and starting to emphasize sustainability in daily activity especially in the agriculture sector. On 7th April 2017, EU Parliament has been approved about EU Resolution where 640 approved, 18 objected and 28 abstained on that resolution. EU Resolution is discussed about to stop deforestation in the tropics and ban the use of non-sustainable vegetable oils for biofuels by 2020 and allow only certified sustainable palm oil to be exported into the EU after 2020. This study is to expose the factors influencing implementation MSPO among independent smallholder. This study covers education level, perceived benefit, age and government support as independent variable. A total 60 respondents from smallholder at Tangkak, Johor was taken in the program with MPOB. Results showed that all the variables are the positive relationship. Meanwhile, education level and age factor show weak relationship, perceived benefit show moderate relationship and government support shows a strong relationship toward dependent variable that is implementation. Government support is very important in implementation of MSPO. Therefore, support from government such as RM130 million as MSPO funds will help independent smallholder to make sure this national palm oil sustainability certification system will be become a reality.